Experiences of South African women in agile projects: an intersectional perspective - Ngwadla, Sinethemba (Department of Information Systems, 2026)
Gender diversity remains a significant challenge in the Information Technology (IT) industry, particularly in South Africa, where the workforce composition does not reflect the nation's demographic diversity. This disparity results in the underrepresentation of women despite policies aimed at fostering inclusion. Existing research highlights a decline in women's participation in the IT sector but often overlooks the perceptions and treatment of women within IT workplaces. This study investigates women's experiences working in Agile project environments in South African IT companies. Agile is a popular software development methodology emphasizing collaboration, communication, and collective decision-making. Using intersectionality theory, this cross-sectional study examines how gender and background factors affect women's work performance. Data were collected through semi-structured interviews with twenty-five women IT professionals recruited via snowball sampling. Key findings indicate that gender discrimination persists in Agile environments. The study revealed that South African women in Agile project environments exist within a male dominated, Gendered Organisational Culture, which privileges behaviours and actions that benefit men. Women in these environments often experience feelings of inadequacy due to their minority status in predominantly male teams. Other specific persistent issues emerged such as gendered recognition bias, gender pay gap, job insecurity, lack of support for motherhood, work-life balance, and scarcity of women mentors. The study further reveals that the high attrition rate of women in IT is not due to the technical demands of the roles but rather the negative impact of organisational culture and gender bias on their professional development. The study's limitations include its reliance on a small, non-random sample, which may not fully represent the broader population. Additionally, the focus on Agile environments may limit the generalizability of the findings to other IT settings. Future research should explore the intersection of gender with other factors, such as socioeconomic status and motherhood, providing a more comprehensive understanding of the barriers women face in IT. It should also investigate strategies to create more inclusive and supportive workplace cultures.